Revisiting Optical Reflectance from Au(111) Electrode Surfaces with Combined High-Energy Surface X-ray Diffraction. Issue 9 (23rd September 2021) - Linpé, Weronica; Rämisch, Lisa; Abbondanza, Giuseppe; Larsson, Alfred; Pfaff, Sebastian; Jacobse, Leon; Zetterberg, Johan; Merte, Lindsay; Stierle, Andreas; Hegedues, Zoltan; Lienert, Ulrich; Lundgren, Edvin; et al.
Abstract : We have combined high-energy surface X-ray diffraction (HESXRD) with 2D surface optical reflectance (2D-SOR) to perform in situ electrochemical measurements of a Au(111) electrode in 0.1 M HClO4 electrolyte. We show that electrochemically induced changes to Au(111) surface during cyclic voltammetry can be simultaneously observed with 2D-SOR and HESXRD. We discuss how small one atom high 1x1 islands, accommodating excess atoms after the lifting of the surface reconstruction, can lead to discrepancies between the two techniques. The use of HESXRD allows us to simultaneously detect parts of the truncation rods from the (1 × 1) surface termination and the p x √3 electrochemically induced surface reconstruction, during cyclic voltammetry. The presence of reconstruction phenomena is shown to not depend on having an ideally prepared surface and can in fact be observed after going to very oxidizing potentials. 2D-SOR can also detect the oxidation of the Au surface, however no oxide peaks are detected in the HESXRD signal, which is evidence that any Au oxide is X-ray amorphous.